Synergistic Behavior of Polyethyleneimine and Epoxy Monomers Loaded in Mesoporous Silica as a Corrosion-Resistant Self-Healing Epoxy Coating - Muddasir Nawaz (17052438) (2022)
Corrosion is a significant problem and is, to a large extent, responsible for the degradation of metallic parts. In this direction, mesoporous silica particles (MSPs) were synthesized by a sol–gel technique and had an average pore diameter of ∼6.82 nm. The MSPs were loaded with polyethyleneimine (PEI) and epoxy monomers and, after that, carefully mixed into the epoxy matrix to formulate new modified polymeric coatings. The microstructural, compositional, structural, and thermal properties were investigated using various characterizing tools [Transmission electron microscopy, Fourier transform infrared spectroscopy, hermogravimetric analysis (TGA), and X-ray photoelectron spectroscopy]. TGA confirms the loading of mesoporous silica with a corrosion inhibitor, and its estimated loading amount is ∼8%. The electrochemical impedance spectroscopy properties of the reference and modified coated samples confirm the promising anti-corrosive performance of the synthesized polymeric smart coatings. Localized electrochemical tests (scanning vibrating electrode technique and scanning ion-selective electrode technique) evidence the corrosion inhibition ability of the coating, and its self-healing was also observed during 24 h of immersion. The decent anti-corrosion performance of the modified coatings can be credited to the efficient synergistic effect of the PEI and epoxy monomer. Other Information Published in: ACS Omega License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1021/acsomega.2c01508